2022
DOI: 10.1111/jfpp.17253
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic coffee ice cream as an innovative functional dairy food

Abstract: Coffee is one of the most popular beverages in the world due to its energizing caffeine effects, pleasant sensory qualities, and positive implications on human health. According to Statista (2021), around 9997.8 million kilograms of coffee were consumed globally in 2020/2021, representing a modest rise over the previous year (1.6%). Coffee contains more than 50% carbohydrates, 10% proteins, and 2% free amino acids and polyphenols. As a consequence of caffeine's content, those responsible for physiological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…, 2020). Probiotic coffee ice cream made using concentrated coffee extract along with probiotic cultures such as Bifidobacterium breve Bb-12 and Lactobacillus plantarum displayed strong antioxidant and antimicrobial activity due to phenolic compounds (Ahmed et al. , 2022).…”
Section: Technological and Physico-chemical Aspects Of Probiotic Ice ...mentioning
confidence: 99%
“…, 2020). Probiotic coffee ice cream made using concentrated coffee extract along with probiotic cultures such as Bifidobacterium breve Bb-12 and Lactobacillus plantarum displayed strong antioxidant and antimicrobial activity due to phenolic compounds (Ahmed et al. , 2022).…”
Section: Technological and Physico-chemical Aspects Of Probiotic Ice ...mentioning
confidence: 99%
“…In this sense, incorporating coffee extracts into functional yogurt deserves attention. Coffee, a globally appreciated beverage with documented health benefits [64], not only presents a distinctive flavor but also possesses antioxidant, anticarcinogenic, and antiinflammatory properties [65]. Its composition includes caffeine, chlorogenic acids, and melanoidins [66], giving the yogurt matrix a unique flavor profile.…”
Section: Probiotic Functional Yogurts Enriched With Natural Compoundsmentioning
confidence: 99%
“…[64][65][66]68,95,96], cocoa polyphenols[79][80][81][82]97,98], turmeric[84][85][86]99], saffron[87][88][89][90][91]100,101], and Spirulina spp [70,71,74,75,[102][103][104][105]. in foods are established, which can be visualized in Figure2.…”
mentioning
confidence: 99%
“…Recent works have suggested that CGA can inhibit the biofilm formation, aggregation and quorum sensing (QS) systems of Pseudomonas [22,23]. On the other hand, CGA is practically non-degradable in the presence of probiotics, which makes it appropriate for use in the food industry [24].…”
Section: Introductionmentioning
confidence: 99%